Ovine feed intake, digestibility, and nitrogen balance in feeds containing different amounts of cupuaçu meal - Laurena Silva Rodrigues; Bruno Peres Menezes; André Guimarães Maciel e Silva; Cristian Faturi; Jamile Andréa Rodrigues da Silva; Alexandre Rossetto Garcia; Benjamim de Souza Nahum; Stéfano Juliano Tavares de Andrade; José de Brito Lourenço Junior (Semina: Ciências Agrárias, 2015)
Twenty neutered male sheep were subjected to 26 days of a metabolic assay at Embrapa Eastern Amazon in Belém, PA, Brazil (01°26’02”S and 48°26’21”W; altitude 8 m). The trial followed a completely randomized design, with five treatments and four repetitions. Treatment A (control) consisted of a diet containing 100% grass. The diet in treatment B contained 10% CM and 90% grass; that in treatment C contained 20% CM and 80% grass; that in treatment D contained 40% CM and 60% grass; and that in treatment E contained 60% CM and 40% grass. Intake of experimental diet and apparent digestibility coefficient of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ethereal extract (EE), cellulose (CEL), hemicellulose (HEM), and nitrogen balance (NB) were assessed. Results showed that the level of CM replacement significantly affected intake of mineral matter (IMM), crude protein (ICP), ethereal extract (IEE), and cellulose (ICEL), with the highest (P < 0.05) values of IMM, ICP, and IEE being observed for feed in which 60% of grass was replaced by CM, indicating that the acceptance of the experimental diet was good. ICEL decreased as levels of CM replacement increased. At 40% replacement, the apparent DM digestibility coefficient was the lowest (41.54%) and did not statistically differ from diets with 60% (45.74%) and 20% (54.19%) CM replacement. The lowest values for the apparent digestibility coefficients of OM, CP, NDF, and ADF were observed when grass was replaced with 40% and 60% CM. For diets with up to 20% replacement of Mombaça grass by CM, the apparent digestibility coefficients of DM, OM, NDF, and ADF were the highest and did not significantly differ from those of the control treatment. Nitrogen excretion in feces differed significantly; the lowest values were found with 0%, 10%, and 20% CM replacement. Use of CM represents an alternative method of dietary supplementation for ruminants and is a good source of protein and energy, since replacing Mombaça grass with increasing levels of CM led to an increase in the voluntary feed intake by ovines.